Promoting Private Conservation in Patra Seroja Ecopark, Dumai Municipality, Riau Province, Indonesia - Budiman, Mokhamad Asyief Khasan; Christian, Yoppie; Afandy, Andy; Prabowo, Budi; Desmiwati , Desmiwati (Foresty Faculty of Hasanuddin University, 2025)
This paper documents the voluntary conservation practices in Patra Seroja Ecopark Forest by Indonesia’s state-owned oil and gas company, Pertamina Ltd. - Refinery Unit II Dumai, Province of Riau, west coast of Sumatera Island. The company voluntarily allocated, financed, and managed 102 hectares of land in their private area to conserve and protect its in-situ biodiversity and preserve environmental service as a secondary objective. The results of studies and assessments carried out, the management application has fulfilled the Privately Protected Area (PPA) management criteria by IUCN regarding the orientation, biodiversity, management model, and utilization. However, PPA is not recognized legally as an addition to traditionally government-led governance of conservation forests in Indonesia: KSA (Nature Reserve Area), KPA (Nature Conservation Area), TB (Hunting Park) model. Considering the potential width of Privately Protected Area application in Indonesia to support national target achievement on Convention on Biological Diversity (CBD) and Aichi 11 Target and fostering the voluntary initiatives by private in conserving biodiversity, the state may recognize the practices and initiate the legal instrument for PPA application in Indonesia.